Intestinal parasitic infections and associated epidemiological drivers in two rural communities of the Bolivian Chaco - Fabio Macchioni; Higinio Segundo; Valentina Totino; Simona Gabrielli; Patricia Rojas; Mimmo Roselli; Grover Adolfo Paredes; Mario Masana; Alessandro Bartoloni; Gabriella Cancrini (Journal of Infection in Developing Countries)
Introduction: In 2013 a coproparasitological survey was carried out in two rural communities of the Bolivian Chaco to determine the prevalence of intestinal parasitic infections (IPIs) and to investigate on possible infection drivers through a questionnaire interview. Methodology: Faecal samples were examined by microscopy. Samples positive for Entamoeba histolytica complex and Blastocystis were molecularly examined to identify the species/subtypes involved. Results: The overall infection rate was 86%, identical in both communities and mostly due to protozoa. Soil-transmitted helminths were detected in <3% of children and adults. Discussion: The protozoa detected, including Blastocystis subtypes, indicate faecal contamination of the environment by both humans (as confirmed by the presence of Hymenolepis nana) and animals. Nested-PCR identified E. histolytica, thus signalling the possible occurrence of invasive amoebosis. Lack of safe water, environmental contamination, poor sanitation and hygiene, shared by both communities, are the main drivers of IPIs. In addition, unlike gender and socioeconomic factors, childhood (only for some species), crowding and cohabitation with animals proved to be further significant protozoon infection risk factors. Conclusions: These results highlight the need for the promotion of access to clean water, improved sanitation and better hygiene, thus reducing the frequency of preventive chemotherapy for STHs while continuing to monitor the population for possible recrudescence.